2020
DOI: 10.1039/c9sc05997k
|View full text |Cite
|
Sign up to set email alerts
|

Combination of chemotherapy and oxidative stress to enhance cancer cell apoptosis

Abstract: The 1,2-diselenolane unit is a general scaffold to construct glutathione-dependent prodrugs that show increased potency to cancer cells, and work via a combination of chemotherapy and oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 64 publications
3
47
0
2
Order By: Relevance
“… 107 1,2-Dithiolane probes, such as 34 , that turn on fluorescence (or release drugs) upon reductive opening as outlined in 35 , have been quite extensively explored by Fang and co-workers. 108 110 The puzzling relation of specific thioredoxin labeling with 34 and thiol-mediated uptake is being addressed by Thorn-Seshold and co-workers. 111 …”
Section: Privileged Scaffoldsmentioning
confidence: 99%
“… 107 1,2-Dithiolane probes, such as 34 , that turn on fluorescence (or release drugs) upon reductive opening as outlined in 35 , have been quite extensively explored by Fang and co-workers. 108 110 The puzzling relation of specific thioredoxin labeling with 34 and thiol-mediated uptake is being addressed by Thorn-Seshold and co-workers. 111 …”
Section: Privileged Scaffoldsmentioning
confidence: 99%
“…Chemotherapy-induced oxidative stress plays a controversial role in cancer and has raised some concerns regarding the effectiveness of combinatorial approaches ( Shacter et al, 2000 ; Liu and Wang, 2015 ; Li et al, 2020 ). A recent study suggested that oxidative stress could be another contributor to PDAC desmoplasia in the sense that it can induce p38-mediated monocyte-to-myofibroblast transdifferentiation (MMT), thereby leading to stromal activation, modulating immunosuppression, as well as promoting tumor progression ( Huang et al, 2020 ).…”
Section: The Effects Of Cancer Therapies On Cancer-associated Fibroblastsmentioning
confidence: 99%
“…Functionally, in addition to the key role of TrxR in redox regulation 20,21 , an ever-widening range of evidence has supported that TrxR highly enriched in many tumor types is essentially implicated with multiple steps of tumorigenesis and development [20][21][22][23] , and is a potential and promising target for the current anticancer drugs discovery [24][25][26][27] . As our continuing efforts in discovering therapeutic molecules derived from natural products that effectively interfere with cellular redox signaling [28][29][30][31][32][33][34][35][36][37][38][39] , we assessed herein the antitumor activity of ONP, C2 and C3, and systematically reported a new mechanism by which ONP targets intracellular TrxR inhibition to cause oxidative stress-mediated tumor cell apoptosis. Mechanistically, the b-carbocation of the lactone ring in ONP covalently bound to the redox-active Sec residue at the C-terminus of TrxR, thereby leading to a decrease in TrxR activity.…”
Section: Introductionmentioning
confidence: 99%